Philosophy, Mind, and Cognitive Inquiry
XII, 450 p.
Keywords: This series will include monographs and collections of studies devoted to the investigation and exploration of knowledge, information, and data-processing systems of all kinds, no matter whether human. (other) animal, or machine. Its scope is intended to span the full range of interests from classical problems in the philosophy of mind and philosophical psychology through issues in cognitive psychology and sociobiology (concerning the mental capabilities of other species) to ideas related to artificial intelligence and computer science. While primary emphasis will be placed upon theoretical, conceptual, and epistemological aspects of these problems and domains, empirical, experimental, and methodological studies will also appear from time to time. No problem within the field of cognitive inquiry is more difficult than that of developing an adequate conception of the nature of mind and of its mode of operation. Our purpose in compiling the present volume has been to contribute to the pursuit of this objective by bringing together a repre sentative cross-section of the principal approaches and the primary players who are engaged in contemporary debate on these crucial issues. The book begins with a comprehensive introduction composed by David Cole, the senior editor of this work, which provides a background for understanding the major problems and alternative solutions, and ends with a selected bibliography intended to promote further research. If our efforts assist others in dealing with these issues, they will have been worthwhile. J. H. F. David J. Cole et at. (eds. ), Philosophy, Mind, and Cognitive Inquiry, ix.